2016
DOI: 10.1159/000452531
|View full text |Cite
|
Sign up to set email alerts
|

Phase II/III Study of Radiofrequency Ablation Combined with Cytokine-Induced Killer Cells Treating Colorectal Liver Metastases

Abstract: Purpose: This phase II/III, non-randomized clinical trial aimed to determine the efficacy and safety of the combination of radiofrequency ablation (RFA) and cytokine-induced killer (CIK) cells transfusion for patients with colorectal liver metastases (CRLMs). Experimental Design: A total of 60 eligible patients with CRLMs were enrolled and divided into Group A (RFA alone, n = 30) and Group B (RFA plus CIK, n = 30), and following enzyme-linked immunosorbent spot assay was performed in 8 patients with CEA > 50 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…CIK cell-based immunotherapy is effective for metastatic CRC, as demonstrated by improved OS and progression-free survival rates. 16 , 52 Moreover, researchers have demonstrated that the infusion of DC vaccine and CIK cells can induce a strong immune response with a positive response of delayed-type hypersensitivity (DTH) in cancer patients, such as those with advanced renal cell carcinoma, hepatocellular carcinoma, and pancreatic cancer. 45 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…CIK cell-based immunotherapy is effective for metastatic CRC, as demonstrated by improved OS and progression-free survival rates. 16 , 52 Moreover, researchers have demonstrated that the infusion of DC vaccine and CIK cells can induce a strong immune response with a positive response of delayed-type hypersensitivity (DTH) in cancer patients, such as those with advanced renal cell carcinoma, hepatocellular carcinoma, and pancreatic cancer. 45 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…The use of autologous and allogeneic CIK cells in combination with curative therapy has thus far yielded mixed responses. For the treatment of 60 patients with colorectal liver metastases, autologous CIK cell transfer 1 week following RFA showed higher median PFS (23 vs 18.5 months), 3‐year progression‐free rates (20.3% vs 13.3%), and 3‐year survival rates (81.0% vs 64.6%) relative to the control group not receiving CIK cell transfer 71 . In a phase 3 clinical trial for the treatment of hepatocellular carcinoma (HCC), autologous CIK cell transfer after liver resection did not improve disease‐free survival (DFS) or OS, but prolonged the median time in therapeutic range (TTR) in a total of 200 patients (13.6 vs 7.8 months) 72 .…”
Section: Cik Cellsmentioning
confidence: 96%
“…Radiofrequency ablation (RFA) is an established treatment for CRC liver metastases, and by heating the tissue, RFA induces coagulation necrosis, leading to a strong inflammatory response (59). One study has investigated the efficacy and safety of the combination of RFA and cytokineinduced killer (CIK) cell transfusion for patients with CRC liver metastases (60). Compared to RFA alone, the median PFS is 23 months with the combination versus 18.5 months with RFA alone.…”
Section: Other Treatment Modalitiesmentioning
confidence: 99%